2017
DOI: 10.1111/jne.12462
|View full text |Cite
|
Sign up to set email alerts
|

Impaired learning and memory in rats induced by a high‐fat diet: Involvement with the imbalance of nesfatin‐1 abundance and copine 6 expression

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease, resulting not only in liver dysfunction, glucose and lipid metabolism disorder, but also in neuropsychiatric damage. In the present study, a NAFLD rat model was established via feeding of a high-fat diet, and behaviour was observed via the open field test (OFT), the sucrose preference test (SPT), the elevated plus maze (EPM), the forced swimming test (FST) and the Morris water maze (MWM). The plasma concentrations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 52 publications
10
20
0
Order By: Relevance
“…Despite the animals in groups P and especially those in group G showing less weight gain after 72 or 182 days treatment, the behavior in EPM was similar to animals in groups C, GL and L. These data match those in the literature when animals were treated with a diet rich in sucrose [5,6], rich in protein [20] and rich in lipids [7,9,10,16] and also showed no change when tested in the EPM. However, the diet rich in lipids had an anxiolytic [13] and anxiogenic effect [11,12,14,15,17].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Despite the animals in groups P and especially those in group G showing less weight gain after 72 or 182 days treatment, the behavior in EPM was similar to animals in groups C, GL and L. These data match those in the literature when animals were treated with a diet rich in sucrose [5,6], rich in protein [20] and rich in lipids [7,9,10,16] and also showed no change when tested in the EPM. However, the diet rich in lipids had an anxiolytic [13] and anxiogenic effect [11,12,14,15,17].…”
Section: Discussionsupporting
confidence: 87%
“…The assessment of anxiety in animals treated with obesogenic diets (rich in carbohydrates [5,6], lipids [7][8][9][10][11][12][13][14][15][16][17] and carbohydrates and lipids [18,19]) is controversial. For some authors, the diet did not change the behavior in the EPM [5][6][7]9,10,16,20], for others it increased [8,11,12,14,15,[17][18][19] or reduced anxiety [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that nesfatin-1 is widely expressed in these anatomical structures in the brain (20). In a previous study ,Chen et al suggested that nesfatin-1 has a moderating effect on learning and memory in rats (21) and from this point of view, higher serum levels of nesfatin-1 in Alzheimer's patients may be associated with this effect.…”
Section: Discussionmentioning
confidence: 95%
“…Insulin is an active substance with a variety of biological functions that affect growth and apoptosis in neurons by participating in blood glucose metabolism [ 3 8 ]. The discovery of insulin in the brain suggested that insulin not only participates in metabolism and growth but is also involved in higher cognitive functions, such as learning and memory [ 3 – 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin is an active substance with a variety of biological functions that affect growth and apoptosis in neurons by participating in blood glucose metabolism [ 3 8 ]. The discovery of insulin in the brain suggested that insulin not only participates in metabolism and growth but is also involved in higher cognitive functions, such as learning and memory [ 3 – 5 ]. Insulin has been shown to increase the expression of amyloid precursor protein (APP), beta-amyloid 42 (A β 42), and hyperphosphorylated tau in the hippocampus and frontal cortex in rats [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%